ANALISA PENGARUH MEDIA KONEKSI DAN TEMPAT AKSES INTERNET TERHADAP PRESTASI BELAJAR SISWA SMA DI WONOGIRI - Bambang Satrionugroho; Sri Tomo (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
Problems that are often faced by senior secondary schools in the learning process that utilize information technology include the limitations of learning facilities and infrastructure, human resources and also learning resources. This study aims to determine the benefits of the internet, especially in terms of the media used to access the internet and where to access the internet in influencing student achievement in Wonogiri. In this study used the method of distributing questionnaires for data collection, validity testing, and reliability testing and descriptive statistics, followed by hypothesis testing with linear regression. And the results of the study show that the media to access the internet and the places chosen to access the internet together have a positive effect on improving student learning achievement.Keywords: senior secondary school, student achievement, linear regression.